Who wins in a complex buyer-supplier relationship? A social exchange theory based dyadic study. Issue 4 (2nd April 2015) - Tanskanen, Kari
Abstract : Purpose: – In complex buyer-supplier relationships (BSRs), contracts are always incomplete and many of the exchanges non-contractual. Because they occur over a long period of time and include unspecified obligations, non-contractual exchanges might be asymmetrical. The purpose of this paper is to examine BSRs with the aim of identifying the mechanisms that lead to asymmetry in exchanges. Design/methodology/approach: – The author conducts an analysis, based on social exchange theory (SET), of six buyer-supplier dyads using the main SET constructs. From this multiple-case analysis the author develops a set of propositions explaining the exchange asymmetry in complex buyer-supplier relations. Findings: – The results indicate that self-awareness of the determinants of attractiveness, use of power-balancing mechanisms, and primacy can explain the exchange asymmetry in BSRs. Research limitations/implications: – The analysis is limited on the explanations for exchange asymmetry that are based on SET. Practical implications: – The study highlights the importance of firms using the power-balancing mechanism in order to gain value from supply chain partners. The results show that firms can use attractiveness strategically to influence supply chain partners, but the author also observe that firms generally are not well aware of the determinants of their attractiveness in BSRs, which ignorance may pose a major obstacle to using attractiveness strategically. Originality/value: – The paper provides the first systematic and comprehensive insight to social exchange mechanism in complex BSR. In this paper the author makes a major effort to clarify the basic assumptions and scope of the useful concepts and theoretical constructs of SET, and through a multiple-case study the author form a piece of substantive theory of SET in BSRs.